Analisis Strenght Weakness Opportunity Threat (SWOT) Dalam Menentukan Strategi Pemasaran Penjualan Roti - Dewita Sari (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2020)
The purpose of this study is to find out and analyze the right strategy in increasing sales volume at the